Characterization of sodium alginate-based films incorporated with thymol for fresh-cut apple packaging. (August 2021) - Chen, Jingxin; Wu, Ankang; Yang, Mingliang; Ge, Yonghong; Pristijono, Penta; Li, Jianrong; Xu, Baocheng; Mi, Hongbo
Abstract: The non-antibacterial and relatively poor mechanical properties of sodium alginate film limit its application for fresh-cut fruit packaging. The phenolic compound thymol has prominent antioxidant and antibacterial activities. The physical and functional properties of thymol/sodium alginate composite films and their ability to preserve fresh-cut apples were investigated. Thymol/sodium alginate composite films were observed to have high tensile strength, elongation at break and UV–vis light blocking capability, but low water vapor permeability, water solubility, and swelling ratio compared with standard sodium alginate film without thymol. The composite films also showed notable scavenging activity against 1, 1-diphenyl-2-picrylhydrazyl radicals. In addition, the composite films exhibited remarkable inhibition of the growth of Staphylococcus aureus and Escherichia coli . Furthermore, thymol/sodium alginate films could effectively reduce weight loss, retain nutrition and surface color of fresh-cut apple slices. Therefore, sodium alginate films with thymol have strong potential as a cling wrap material used in the packaging of fresh-cut fruits. Highlights: A moderate amount of thymol can improve the properties of sodium alginate film. Thymol can endow antioxidant and antibacterial activities to sodium alginate film. The composite film has good effects on extending the shelf-life of fresh-cut apple.